Differences in microbial etiology between hospital-acquired pneumonia and ventilator-associated pneumonia: a single-center retrospective study in Guang Zhou - Feng, Ding-Yun (Infect Drug Resist, 2019)
Purpose: Nosocomial pneumonia is a common nosocomial infection that includes hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia(VAP). It is an important cause of morbidity and mortality in hospitalized patients. This study aimed to evaluate the differences in microbial etiology and outcomes between HAP and VAP, particularly in related risk factors of multidrug-resistant organism (MDRO) causing HAP and VAP. Patients and methods: This single-center retrospective, observational study included patients with HAP/VAP. Clinical and epidemiological data of nosocomial pneumonia confirmed by microbial etiology that occurred in the Third Affiliated Hospital of Sun Yat-sen University, China, from January 2014 to December 2017 were obtained. Results: A total of 313 HAP cases and 106 VAP cases were included. The leading pathogens of HAP and VAP were similar, including Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Antimicrobial susceptibility of the pathogens was low, and P. aeruginosa in VAP was less susceptible. In the multivariate logistic regression analysis, the risk factors associated with MDRO-HAP were chronic obstructive pulmonary disease, antibiotic therapy in the preceding 90 days, and prior endotracheal tracheostomy. The risk factor of MDRO-VAP was ≥5 days of hospitalization. The 30-day mortality rates of HAP and VAP were 18.5% and 42.5%. Conclusion: The leading pathogens were similar in both HAP and VAP, and antimicrobial susceptibility of the pathogens was low. The risk factors associated with MDRO infection in HAP and VAP have significant variability; hence, attention should be paid to improve prognosis. VAP was associated with poorer outcomes compared with HAP.